High temperature mechanical behavior of ceramic composites - Nair, Shantikumar Vasudevan, 1953-; Jakus, Karl
High Temperature Mechanical Behavior of Ceramic Composites provides an up-to-date comprehensive coverage of the mechanical behavior of ceramic matrix composites at elevated temperatures. Topics include both short-term behavior (strength, fracture toughness and R-curve behavior) and long-term behavior (creep, creep-fatigue, delayed failure and lifetime). Emphasis is on a review of fundamentals and on the mechanics and mechanisms underlying properties. This is the first time that complete information of elevated temperature behavior of ceramic composites has ever been compacted together in a sin.